2009
DOI: 10.1021/jm8014124
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of XL335 (WAY-362450), a Highly Potent, Selective, and Orally Active Agonist of the Farnesoid X Receptor (FXR)

Abstract: Azepino[4,5-b]indoles have been identified as potent agonists of the farnesoid X receptor (FXR). In vitro and in vivo optimization has led to the discovery of 6m (XL335, WAY-362450) as a potent, selective, and orally bioavailable FXR agonist (EC(50) = 4 nM, Eff = 149%). Oral administration of 6m to LDLR(-/-) mice results in lowering of cholesterol and triglycerides. Chronic administration in an atherosclerosis model results in significant reduction in aortic arch lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(99 citation statements)
references
References 27 publications
5
92
0
Order By: Relevance
“…In this study, although the steady levels of plasma HDL are reduced, activation of FXR results in enhanced HDL cholesterol transport to the feces. Consistent with our observations, more recent studies demonstrated that treatment of hyperlipidemic Ldlr Ϫ/Ϫ or Apoe Ϫ/Ϫ mice with FXR agonists resulted in a decrease in atherosclerotic lesions (8,36,37). These latter changes may result, at least in part, from increased RCT by SR-BI-dependent and -independent pathways, as well as a decrease in intestinal cholesterol absorption.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, although the steady levels of plasma HDL are reduced, activation of FXR results in enhanced HDL cholesterol transport to the feces. Consistent with our observations, more recent studies demonstrated that treatment of hyperlipidemic Ldlr Ϫ/Ϫ or Apoe Ϫ/Ϫ mice with FXR agonists resulted in a decrease in atherosclerotic lesions (8,36,37). These latter changes may result, at least in part, from increased RCT by SR-BI-dependent and -independent pathways, as well as a decrease in intestinal cholesterol absorption.…”
Section: Discussionsupporting
confidence: 92%
“…However, bile acids can also stimulate other pathways in an FXR-independent manner (5). In contrast, synthetic FXR agonists, such as GW4064 (6), fexaramine (7), or WAY-362450 (8), specifically activate FXR. The expression of FXR is restricted to the liver, kidney, intestine, and adrenal glands (9 -12).…”
mentioning
confidence: 99%
“…On the other hand, FXR defi ciency in LD-LR-defi cient mice is atheroprotective ( 61,62 ). The effect of FXR activation on decreasing atherosclerotic plaque burden seems in part due to an improvement of the lipid profi le (63)(64)(65).…”
Section: Fxr and Atherosclerosismentioning
confidence: 99%
“…Mice, hamsters, and rats were treated with various FXR agonists that differed in structure and affi nity for the human and murine FXR LBD as shown in Table 1 and described in the literature (35)(36)(37). Whereas all of the fully synthetic and selective FXR agonists bound to the human and murine FXR LBD with IC 50 s of р 0.21 M and р 1.1 M, respectively, 6-ECDCA was 18-and 9-fold less potent, respectively and TCA was inactive against human FXR up to the highest concentration used (100 M).…”
Section: Potency and Selectivity Of Fxr Ligandsmentioning
confidence: 99%